Finite element elastoplastic homogenization model of a corrugated-core sandwich structure - Luong, Viet D.; Abbes, Fazilay; Hoang, Minh P.; Duong, Pham T. M.; Abbes, Boussad (Steel and Composite Structures, 2021)
This study aimed to develop an elastoplastic homogenization model to accurately predict the elastoplastic static behavior of a corrugated-core sandwich structure. A panel composed of two planar layers and one corrugated layer is modeled by a homogeneous orthotropic single-layer plate. A plane stress elastoplastic model is adopted to describe the behavior of each layer. Homogenization is achieved by local integration across the thickness of each layer. The proposed homogenization model is implemented in the ABAQUS finite element software using UGENS user subroutine. The results obtained by our model are compared to those obtained by full 3D simulations under different loading conditions. The comparisons show the efficiency and the accuracy of the proposed elastoplastic homogenization model.